2011
DOI: 10.1155/2011/525976
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Alcohol, and Betel Quid and Oral Cancer: A Prospective Cohort Study

Abstract: We aimed to investigate the association between smoking, alcoholic consumption, and betel quid chewing with oral cancer in a prospective manner. All male patients age ≥18 years who visited our clinic received an oral mucosa inspection. Basic data including personal habits were also obtained. A multivariate logistic regression model was utilized to determine relevant risk factors for developing oral cavity cancer. A total of 10,657 participants were enrolled in this study. Abnormal findings were found in 514 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 18 publications
8
95
3
1
Order By: Relevance
“…Risk of OSCC for alcohol consumers was relatively much lower than tobacco chewers and smokers. A study by Lin et al (2011) supported to our findings. Some previous studies reported that a great risk of oral cancer in consumers who chewing tobacco and kept in the mouth for different duration of time, depending on the personal habits (Muwonge et al, 2008;Madani et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Risk of OSCC for alcohol consumers was relatively much lower than tobacco chewers and smokers. A study by Lin et al (2011) supported to our findings. Some previous studies reported that a great risk of oral cancer in consumers who chewing tobacco and kept in the mouth for different duration of time, depending on the personal habits (Muwonge et al, 2008;Madani et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…The epidemiological study of oral cancer in Asia indicated that some common factors like use of tobacco, alcohol and quid chewing are the main reasons for the increasing incidence of oral cancer in Asian countries (Krishna Rao et al, 2013). The prevalence of smoking in OSCC group in this study was 50%, which is higher than that in other studies (Lin et al, 2011). However, selection bias is unavoidable in case-control studies.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies conducted suggests that the risk factors which are seen to have a significant association with oral cancer are tobacco, alcohol and human papilloma virus (Lin et al, 2011a). Investigators comment that alcohol and smoking are accountable for 80% of the cases in males, 61% of the cases in females and 74% overall (Warnakulasuriya et al, 2005;Gillison, 2007 andPetersen, 2009).…”
Section: Introductionmentioning
confidence: 99%